Philosophical Problems of Modern Physics - Mittelstaedt, Peter. author. aut Link
X, 211 p. 1 illus.
Keywords: Professor Peter Mittelstaedt is a physicist whose primary concern is the foundations of current physical theories. This concern has made him, through his prolonged, incisive and detailed examinations of the structures and overall characteristics of these theories, into a philosopher of physic- of contemporary physics, to be precise, of relativistic theories of space and time, and of the logic of quantum mechanics, in particular. The present book, which expounds his main ideas in these matters, has seen four editions (in German), each including newer results - as indeed does the present translation: see the author's 1975 preface to the English translation. Perhaps this is the place to repeat the author's chief problem and mention his own approach, even though they are expounded in his Intro duction. How close is Mittelstaedt to Kant's understanding of science? We are at liberty to choose a framework for thought - a logic and a method ology - prior to experience (in the classic sense, to think a priori); yet we choose a framework so as to fit our empirical findings. How is this done? How may it be understood and justified? This is obviously the question of all philosophies that evolve from, and are in reaction to, Kant's system.